CHOROIDAL GRANULOMAS VISUALIZED BY ENHANCED DEPTH IMAGING OPTICAL COHERENCE TOMOGRAPHY. Issue 3 (March 2015) - Invernizzi, Alessandro; Mapelli, Chiara; Viola, Francesco; Cigada, Mario; Cimino, Luca; Ratiglia, Roberto; Staurenghi, Giovanni; Gupta, Amod
Abstract : Purpose: To assess the visualization of choroidal granulomas (CG) by enhanced depth imaging optical coherence tomography (EDI-OCT) and to describe their EDI-OCT characteristics. Methods: Combined indocyanine green (ICG) angiography and EDI-OCT images of 44 CG (sarcoid, tubercular, or Vogt–Koyanagi–Harada related) were reviewed. By ICG angiography, CG were classified as full thickness or partial thickness and as small or large. Two independent operators evaluated EDI-OCT scans over granulomas to record their characteristics (full thickness/partial thickness, shape, reflectivity, internal pattern, margins, and shadowing/increased transmission effect). The agreement between ICG angiography and EDI-OCT, the interobserver agreement, and the correlations between EDI-OCT features and lesion size or disease were studied. Results: Enhanced depth imaging optical coherence tomography could visualize 100% of CG detected on ICG. Lesions resulted full thickness in 90.9% and 77.3% of the cases on ICG angiography and EDI-OCT, respectively (K = 0.5). All CG were more homogeneous and showed increased transmission of the optical coherence tomography signal as compared with the surrounding choroid. Choroidal granulomas angiographic size influenced lesions characteristics on EDI-OCT. Large granulomas were more likely to be full thickness, round shaped, with defined margins, lower reflective than the surrounding structures, and with internal homogenous pattern. The type of disease significantly influenced CG shape and pattern. Most of tubercular-related lesions showed lobulated shape and nonhomogeneous internal pattern. Conclusion: Enhanced depth imaging optical coherence tomography is suitable to visualize CG and to describe their characteristics. Choroidal granulomas size and disease influence lesions appearance on EDI-OCT. Increased transmission effect could be helpful for CG identification. Abstract : The study demonstrates the possibility to visualize choroidal granulomas with enhanced depth imaging optical coherence tomography. Choroidal granulomas tomographic characteristics are also reported. Enhanced depth imaging optical coherence tomography can be considered as a useful noninvasive investigation, in addition to indocyanine green angiography, to evaluate choroidal granulomas.